If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4d = 5d + -11 Reorder the terms: 4d = -11 + 5d Solving 4d = -11 + 5d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-5d' to each side of the equation. 4d + -5d = -11 + 5d + -5d Combine like terms: 4d + -5d = -1d -1d = -11 + 5d + -5d Combine like terms: 5d + -5d = 0 -1d = -11 + 0 -1d = -11 Divide each side by '-1'. d = 11 Simplifying d = 11
| 6m-2-9m=1 | | 3.5d+9.25=4+4.25d | | -8=g/4-7 | | 1p+26-10p=1 | | 45-3x=3x | | 2*(9+8)=t | | X^2+10x+m= | | 5(3+2x)-5=40 | | P^2-p-210= | | 15g=1/2 | | 4.2+4e=-8.6 | | (-5y^4-7y-7)+(7y^3+8y+9)=0 | | x^2+11x-100=0 | | (x+6)(1-6)= | | P^2-p-210=0 | | x^2+6x-144=0 | | 8y+8x-8y= | | -6x=-5x-8 | | 2-(1-6r)=6r+1 | | 2/3y^2-4/9y^2= | | x^3=289x | | 8*n=8*5 | | 5x+7=5(x-9) | | 7x-3x+10x= | | 2y-8/-3= | | -23+4b=-5(-4b-6)-5 | | x^2+10x-196=0 | | -5(3x-8)+9=-15+49 | | ln(4x-1)=55 | | 4(5x-1)=2(3x-2) | | 5=-2x-9 | | 3(6x-9)=9(2x-3) |